2023
DOI: 10.1186/s12891-023-06378-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of femoral neck system versus cannulated screws for treatment of femoral neck fractures: a systematic review and meta-analysis

Abstract: Background Recently, some studies on the efficacy of the femoral neck system (FNS) in treating femoral neck fractures (FNFs) have been published. Therefore, a systematic review was performed to clarify the efficacy and safety of FNS versus cannulated screws (CS) for the treatment of FNFs. Method The PubMed, EMBASE, and Cochrane databases were systematically searched for studies comparing FNS and CS fixations in FNFs. Intraoperative indicators, post… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The analysis showed that the occurrence of shortening was concentrated at 3 months postoperatively and basically reached a stable state within 6 months, with less persistent shortening occurring after 6 months. The mean shortening distance at 1 year postoperatively was (6.5 ± 6.4) mm, which was similar to previous reports of mean shortening in the range of 4.9 mm–8.4 mm, and seemed to be consistent with no progression of results at 3 months [ 17 , 21 , 22 ]. The reason may be due to the shortening caused by resorption and plastic modification of the fracture during fracture healing, and secondly, the excessive shortening of the affected limb combined with cortical comminution of the fracture and bone defect due to irrational weight bearing.…”
Section: Discussionsupporting
confidence: 90%
“…The analysis showed that the occurrence of shortening was concentrated at 3 months postoperatively and basically reached a stable state within 6 months, with less persistent shortening occurring after 6 months. The mean shortening distance at 1 year postoperatively was (6.5 ± 6.4) mm, which was similar to previous reports of mean shortening in the range of 4.9 mm–8.4 mm, and seemed to be consistent with no progression of results at 3 months [ 17 , 21 , 22 ]. The reason may be due to the shortening caused by resorption and plastic modification of the fracture during fracture healing, and secondly, the excessive shortening of the affected limb combined with cortical comminution of the fracture and bone defect due to irrational weight bearing.…”
Section: Discussionsupporting
confidence: 90%
“…In summary of the studies so far, FNS seems to be able to significantly reduce femoral neck shortening in particular. In addition, with regard to prognosis, implant‐related complications and osteonecrosis are reduced, and postoperative pain visual analog scales (VAS) and HHS score are also thought to be improved 41 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, with regard to prognosis, implant‐related complications and osteonecrosis are reduced, and postoperative pain visual analog scales (VAS) and HHS score are also thought to be improved. 41 …”
Section: Discussionmentioning
confidence: 99%
“…The importance of an anatomic reduction for a femoral neck fracture is clear, but the optimal implant for fixation remains unclear. A systematic review and meta-analysis compared the femoral neck system with cannulated screws 12 . Eight studies with 448 patients were included.…”
Section: Proximal Femurmentioning
confidence: 99%